2018
DOI: 10.1080/13552600.2018.1504553
|View full text |Cite
|
Sign up to set email alerts
|

“Because you’ve got faith it doesn’t mean that you’ve got wings on your back”: a qualitative analysis of the accounts of Christian prisoners serving time for a sexual offence

Abstract: Because you've got faith it doesn't mean that you've got wings on your back': a qualitative analysis of the accounts of Christian prisoners serving time for a sexual offence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…So why Buddhism? The current study with prisoners who identify as Buddhist is part of a larger research program with individuals of different faiths (see Winder et al 2018;Blagden et al 2018). Research on the link between recidivism and religion has demonstrated a weak association between the two (Johnson 2004): research such as this has, however, led to calls for more research on the impact of religious involvement and, in particular, faith-based treatment programs in prison (see, for example, Thomas and Zaitzow 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So why Buddhism? The current study with prisoners who identify as Buddhist is part of a larger research program with individuals of different faiths (see Winder et al 2018;Blagden et al 2018). Research on the link between recidivism and religion has demonstrated a weak association between the two (Johnson 2004): research such as this has, however, led to calls for more research on the impact of religious involvement and, in particular, faith-based treatment programs in prison (see, for example, Thomas and Zaitzow 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected through semi-structured interviews, which lasted between 1.5 and 3 h. The interview schedule was developed from that used for previous research investigating Christianity within this population (Winder et al 2018), and the questions were adapted to reflect the differences between Buddhism and the Christian faith. The questions were categorized into five main sections:…”
Section: Interviewsmentioning
confidence: 99%
“…The analysis was guided by previous precedents (see Smith, 2015;Blagden et al, 2016;Winder et al, 2019) and entailed detailed reading, re-reading and analysis of each transcript individually by each member of the research team. Themes were identified through a rigorous process whereby the research team members each created a thematic map, which contained between 10 and 13 potential themes or "hubs".…”
Section: Discussionmentioning
confidence: 99%
“…Although in its infancy, this line of academic inquiry is supported by theoretical constructs (Kewley 2019), preliminary research findings supporting the potential contribution of r/s to desistance from sexual offending (Harris et al 2017;Kewley et al 2015;Kewley et al 2017), and self-reports from those who have sexually offended that religion and spirituality are important in their recovery (Geary et al 2004;Geary et al 2006;Robbers 2009;Tewksbury and Mustaine 2009;Tewksbury and Zgoba 2010). Conversely, studies have argued that affiliation with religion can serve to promote criminal behavior when religious doctrine is used to support cognitive distortions that rationalize offending behaviors (Knabb et al 2012;Topalli et al 2012;Winder et al 2018). Despite recent scholarly interest in how r/s might positively or negatively influence desistance, very little is known about how r/s constructs present among those who have sexually offended, or how religious and spiritual struggles might contribute to, or deter from desistance.…”
Section: Religiousness and Spirituality Among Persons Who Have Sexually Offendedmentioning
confidence: 99%